Features of the transition to a remote form of employment of university employees - Yessirkepov, М.М.; Toleubekov, A.T.; Orazov, А.Е. (Bulletin of the Karaganda University “Law Series”, 2023)
During a pandemic, information and communication systems offered new non-standard forms of employment designed to meet the needs of modern society. One of these new flexible forms of employment is “teleworking”, which has already found legislative support in most countries of the world. In this scientific work, the current issues of labour law of the Republic of Kazakhstan for the transition to a remote form of employment of researchers and teachers of higher educational institutions have been studied. In the transition to a remote form, the professional and legal features of this group of employees have been determined. The main task of this study is to identify the main problematic issues in the Labour Code of the Republic of Kazakhstan, affecting the activities of researchers and teachers of higher educational institutions of our country with a natural science profile during the quarantine period and the transition to a remote (distance) form of work. Authors of the article proposed suggestions for supplementing Article 138 “Remote work” of the Labour Code of the Republic of Kazakhstan.